The US-Mexico bilateral trade relation through a value added lens - Armando Aguirre Castro; Diego Cardozo-Medeiros (Banco de México, 2020)
We use the World Input-Output Database and build on Wang et al. (2013) gross exports decomposition to analyze the bilateral trade relation between Mexico and the United States from a value added perspective. Once we take into account that gross commercial flows are clouded by failing to account for imported content, we find that contrary to what gross flows suggest, Mexico has a value added commercial deficit in manufacturing with the United States. Similar patterns can be observed at the sectoral level with significant differences between the gross and value added sectoral trade balances: an improvement of most sectoral US trade balances, particularly for those sectors importing significant amounts of intermediate goods.
Keywords: E1; F2; F14; F15; F23; 330; Global value chains; World input-output tables; International fragmentation of production; Trade imbalances